The Dual Roles of Human γδ T Cells: Anti-Tumor or Tumor-Promoting - Li, Yang; Li, Gen; Zhang, Jian; Wu, Xiaoli; Chen, Xi (Frontiers in Immunology, 2021)
γδ T cells are the unique T cell subgroup whose T cell receptor is composed of γ chain and δ chain. Unlike αβ T cells, γδ T cells are non-MHC-restricted in recognizing tumor antigens, they are considered to be innate immune cells. Activated γδ T cells can promote the activation of adaptive immune cells, thus they are considered as a bridge between adaptive immunity and innate immunity. However, some studies have shown that γδ T cells can promote tumor progression by inhibiting anti-tumor response. Therefore, γδ T cells have both anti-tumor and tumor-promoting effects. In order to clarify this contradiction, in this review, we summarize the main subsets of human γδ T cells and how they play their respective anti-tumor or pro-tumor effects. Then, we reviewed recent γδ T cell-based anti-tumor immunotherapy. Finally, we summarize the existing problems and prospect of this immunotherapy.